ANALYSIS OF FACTORS RELATED TO MEDICATION ADHERENCE IN PATIENTS WITH DIABETES MELLITUS AT RSUI MADINAH KASEMBON - Meilyana, Berna Detha; Suroso, Heri; P, Dimas Eko; Setyawan, Arif; P, Mareta Deka (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Diabetes mellitus is a metabolic disorder characterized by abnormal metabolism of carbohydrates, fats and proteins caused by decreased insulin secretion or decreased insulin sensitivity. Therefore, there is a need for monitoring in therapy management and the need for attention in medication compliance in order to achieve treatment success. The purpose of this study is to find out the analysis of factors related to medication adherence in patients with diabetes mellitus. Methods. This study uses a descriptive correlative cross sectional approach. The sampling technique used purposive sampling and obtained a sample of 142 respondents. The instrument used in the questionnaire. Results and Analysis. The study showed that multivariate analysis using simple linear regression showed that the most influential variable on medication adherence in DM patients was the role of health workers with the results of p = 0.010 and B = 0.553. The role of good health workers will increase compliance by 0.553 times, compared to the role of bad health workers. Adherence to medication is an important value in the success of DM therapy. One of the causes that affects patient compliance in undergoing treatment is poor communication between patients and health workers. Discussion. Health worker support has an important role, namely the delivery of information about health conditions and what patients should do. The attitude and behavior of health workers is a factor that strengthens or encourages the behavior of adherence to treatment in patients.